Output of Volcanic SO2 Gases and Their Dispersion in the Atmosphere: The Case of Vulcano Island, Aeolian Archipelago, Italy - Fabio Vita; Benedetto Schiavo; Claudio Inguaggiato; Jacopo Cabassi; Stefania Venturi; Franco Tassi; Salvatore Inguaggiato (Atmosphere)
Gases emitted from active volcanic systems constitute a primary natural source of global atmospheric pollution. Atmospheric sulfur dioxide (SO2) concentrations were monitored using a near-continuous network based on Scan-DOAS (Differential Optical Absorption Spectroscopy) technology. Complementary intermittent measurements were performed using a UV Thermo® analyzer deployed at fixed locations and along predefined transects on the island. SO2 flux data derived from the Scan-DOAS measurements, coupled with atmospheric dispersion maps generated using the AERMOD modeling software, enabled the estimation of SO2 distribution across the volcanic crater region and inhabited areas of the island, including Vulcano Village and Vulcano Piano. The results of the estimation of SO2 concentration in the atmosphere, integrated with the dispersion modeling, exhibited consistency with direct SO2 concentration measurements obtained by the Thermo® analyzer, demonstrating coherence between the two methodologies, although some overestimations of ambient SO2 were noted. This study provided valuable insights into areas with anomalous SO2 concentrations exceeding the threshold limits established by the World Health Organization (WHO) and the European Union (EU). These limits are generally exceeded in the crater zone and surrounding areas. The findings also highlighted the influence of prevailing winds and the temporal variations in volcanic degassing activity observed over the preceding 17 years, characterized by four periods of unrest degassing with SO2 emission rates from the summit solfataric area reaching up to 250 tonnes per day (td−1).